2009
DOI: 10.1158/0008-5472.can-08-4866
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitors of ABCG2 by a Bioluminescence Imaging–Based High-Throughput Assay

Abstract: ABCG2 is a member of the ATP-binding cassette (ABC) family of transporters, the overexpression of which is associated with tumor resistance to a variety of chemotherapeutic agents. Accordingly, combining ABCG2 inhibitor(s) with chemotherapy has the potential to improve treatment outcome. To search for clinically useful ABCG2 inhibitors, a bioluminescence imaging (BLI)-based assay was developed to allow highthroughput compound screening. This assay exploits our finding that D-luciferin, the substrate of firefly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…It was recently shown by Zhang and colleagues that ABCG2/ BCRP transporters on the cell membrane play a crucial role in D-luciferin retention in the cell. Moreover, they demonstrated that the level of BLI signal from firefly luciferasepositive cells can be influenced by using inhibitors of these transporters [42,43]. Although our data demonstrate that a particle should be intracellular in order to achieve BLI amplification ((i) in Fig.…”
Section: Discussionmentioning
confidence: 66%
“…It was recently shown by Zhang and colleagues that ABCG2/ BCRP transporters on the cell membrane play a crucial role in D-luciferin retention in the cell. Moreover, they demonstrated that the level of BLI signal from firefly luciferasepositive cells can be influenced by using inhibitors of these transporters [42,43]. Although our data demonstrate that a particle should be intracellular in order to achieve BLI amplification ((i) in Fig.…”
Section: Discussionmentioning
confidence: 66%
“…In vitro study showed that ABCG2-overexpressing human NSCLC cell lines were more resistant to chemotherapy (44,45). Inhibition of ABCG2 and/or ABCB1 by selective inhibitors sensitized NSCLCs to chemotherapy (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…To test the relative effectiveness of reported ABCG2 inhibitors in vitro, we measured the bioluminescence signal of HEK cells transfected with fLuc and ABCG2 (23) in the presence of the ABCG2 inhibitors Ko143 (19), tariquidar (24), elacridar (25), gefitinib, or nilotinib (26). The ABCB1 inhibitor (2R)-anti-5-f3-[4-(10,11-dichloromethanodibenzo-suber-5-yl)piperazin-1-yl]-2-hydroxypropoxygquinoline trihydrochloride(DCPQ) (27,28) and HEK cells without ABCG2 (HEK/empty/fLuc) were used as controls.…”
Section: Bioluminescence In Vitro Increases When Coincubated With Abcg2mentioning
confidence: 99%